Cervical microbiota diversity and functional shifts in the development of cervical high-grade squamous intraepithelial lesions - Rosas Cancio-Suárez, Marta; Moreno, Elena; del Valle Rubido, Cristina; Salvador, Marta; Moreno, Ana; Luna, Laura; Díaz-García, Claudio; Tapia, Carlos; del Amo, Ana; Moreno, Santiago; Sánchez-Conde, Matilde; Serrano-Villar, Sergio (Frontiers in Medicine, 2025)
Research on microbial changes in the cervix, where most human papillomavirus (HPV) complications arise, is limited. Here, we aimed to understand the specific role of the cervicovaginal microbiota in developing high-grade squamous intraepithelial lesions (HSIL) associated with HPV infection. Our results show higher diversity in the microbiota associated with HSIL, with the genera Parvimonas, Fastidiosipila, and Pseudomonas being the most abundant. Additionally, an imputed functional analysis revealed that pathways such as glycine, serine, threonine, and sulfur metabolism were enriched in cervical samples from women with HSIL. Identifying biomarkers that help prevent HSIL progression could benefit women at risk of developing HPV-related cancerous lesions.